Design and Development of Continuous Positive Airway Pressure (CPAP) Device - Mahmood, Qusay Abdulwahhab; Sami, Omar Qays; Mohammed, Mona Qasim Kazim; Safar, Sajjad Isam; Alwan, Abbas Riad (American Journal of Botany and Bioengineering, 2025)
Continuous Positive Airway Pressure (CPAP) therapy is a critical intervention for managing sleep-disordered breathing, yet the high cost and limited accessibility of current devices present significant challenges, especially in resource-limited settings. This study addresses these gaps by designing and developing a cost-effective, portable CPAP device with improved functionality. Utilizing an engineering-based approach, the study incorporates design optimization, prototyping, and performance testing to enhance patient comfort, noise reduction, and air pressure stability. Findings demonstrate that the proposed CPAP device effectively maintains airway patency, reduces apnea episodes, and improves sleep quality while ensuring affordability and ease of use. The implications of this research extend to broader applications in home-based and emergency healthcare, offering an innovative solution for individuals with obstructive sleep apnea and other respiratory conditions.